A new quantitative acoustic emission model for damage characterization of composite laminates using original waveforms. (September 2022) - Xu, Dong; Liu, Pengfei; Chen, Zhiping; Wu, Tao
The correlation between acoustic characteristics and mechanical behaviors shows great significance for health monitoring and characterization. This paper develops a new quantitative model based on the modified Mel-frequency cepstral analysis and statistical methods so as to link acoustic emission (AE) features with mechanical behaviors of end-notched flexure (ENF) composite laminates. First, the Mel-frequency cepstral analysis in automatic speech recognition is modified to adapt to AE sensors and signals. Second, the modified Mel-frequency cepstral coefficients (MFCCs) are extracted from original waveforms of AE hits for damage characterization of composites. MFCC0 is taken as an effective feature to qualitatively discriminate damage stages and to identify the pre-failure critical point. The decreasing patterns of MFCC1 and MFCC2 for ENF specimens can be clearly observed with the loading time by using the simple moving average method. Third, pencil lead breaks are repeatedly conducted on the healthy specimen to verify the pattern in the degraded specimen. Finally, a further investigation based on the cumulative moving average method demonstrates that MFCC1 and MFCC2 are quadratic and linear functions of the load ratio or the deflection ratio, respectively. In addition, the latter is more suitable to be an indicator of damage accumulation of composite laminates.